Pengaruh Atraksi Anjungan Tukad Melangit (Atm) Terhadap Pengembangan Desa Wisata Jehem, Kabupaten Bangli - Ni Wayan Surya Muspita Dewi; Ida Ayu Suryasih (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
Jehem Tourist Village has been designated as Tourism Village in 2015. The existence of tourist attraction Anjungan Tukad Melangit (ATM) is currently popular in the eyes of tourists who visit the Village Tourism Jehem. The purpose of this research is to know the condition of existing tourism Jehem Tourism Village and the influence of attraction Anjungan Tukad Melangit (ATM) to the development of Jehem Tourism Village. The data used in this research is qualitative and quantitative data. Primary data source data and secondary data, data method used are: observation, interview and documentation. Informant determination technique used is purposive sampling technique. The results of the research show that the existence of tourist attraction Anjungan Tukad Melangit (ATM) to make tourists began to visit the Village Tourism Jehem. The attraction of Anjungan Tukad Melangit (ATM) has an important influence in the development of Jehem Tourism Village. The advice given in this study is expected to conduct further research in order to provide a deeper knowledge again. Keywords: Jehem Tourist Village, Anjungan Tukad Melangit (ATM), Visits, Influence